Utility of information in package inserts by pharmacists and pharmacy clients in a metropolitan city in Southwest Nigeria (2021)
Objective Package inserts provide relevant information to patients and health care professionals on the safety and rational use of drugs. This study evaluated the utility of package inserts by pharmacy clients for information, and by pharmacists during consultation and counselling with patients. Methods This cross-sectional self-administered questionnaire-based study was conducted in Ibadan, Nigeria among 705 pharmacy clients and 344 community and hospital pharmacists. The questionnaire had a 12-item and a 14-item package insert utility scale for pharmacists and pharmacy clients, respectively. The level of utility and association between demographic variables and package insert utility scores were determined with Mann–Whitney U and Kruskal–Wallis tests at P < 0.05. Key findings The response rate was 88.2% for pharmacy clients and 67.2% for pharmacists. Most of the pharmacy clients, 459 (73.8%), check for package inserts in drug packs. The most assessed information in package inserts was dose 432 (69.5%). Some of the pharmacy clients, 276 (44.4%), considered information from health professionals more reliable than that in package inserts. The pharmacy clients’ level of education was associated with package insert utility score (P = 0.001). Most of the pharmacists, 137 (59.3%), read package inserts but only 36 (15.6%) consulted package inserts during counselling with patients. The pharmacists’ age and the number of years spent in practice were significantly associated with package insert utility scores (P < 0.05). The level of utility of the information in package inserts by the pharmacy clients and the pharmacists was moderate – 66.8 and 60.0%, respectively. Conclusion Both pharmacists and pharmacy clients use package insert content moderately. Pharmacy clients rely more on information provided by health professionals than the information in package inserts but pharmacists seldom consult package inserts during counselling process.